2019
DOI: 10.1108/dprg-11-2018-0068
|View full text |Cite
|
Sign up to set email alerts
|

When the mobile app is free, the product is your personal data

Abstract: Purpose-Mobile devices (smartphones, tables etc.) have become the de facto means of accessing the internet. While traditional Web browsing is still quite popular, significant interaction takes place via native mobile apps that can be downloaded either freely or at a cost. This has opened the door to a number of issues related to privacy protection since the smartphone stores and processes personal data. The purpose of this paper is to examine the extent of access to personal data, required by the most popular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 103 publications
(158 reference statements)
0
22
0
Order By: Relevance
“…Transformative effects Algorithmic activities, like profiling, can lead to challenges for autonomy and informational privacy. For example, Polykalas & Prezerakos, 2019 examined the level of access required to personal data by more than 1000 apps listed in the 'most popular' free and paid for categories on the Google Play Store. They found that free apps requested significantly more data than paid-for apps, suggested that the business model of these 'free' apps is the exploitation of the personal data.…”
Section: Unfair Outcomesmentioning
confidence: 99%
“…Transformative effects Algorithmic activities, like profiling, can lead to challenges for autonomy and informational privacy. For example, Polykalas & Prezerakos, 2019 examined the level of access required to personal data by more than 1000 apps listed in the 'most popular' free and paid for categories on the Google Play Store. They found that free apps requested significantly more data than paid-for apps, suggested that the business model of these 'free' apps is the exploitation of the personal data.…”
Section: Unfair Outcomesmentioning
confidence: 99%
“…The problem becomes even more difficult when there is no price for a service, as in a digital zero-price market (Newman, 2015). A well-known example of a digital zero-price market is Facebook, which leverages personal data to sell personalized ads to other external businesses (Malgieri & Custers, 2018;Polykalas & Prezerakos, 2019). However, not much is said about how these markets really work and how values are exchanged between consumers and businesses.…”
Section: The New Value Creation and Value Capturementioning
confidence: 99%
“…Previous studies therefore lack insight into how value creation and value capture by content creators from a business perspective are carried out. Also, possible value asymmetries between consumers and businesses have been studied within digital zero-price markets (Malgieri & Custers, 2018;Polykalas & Prezerakos, 2019) and other studies have investigated the monetary value (Acquisti et al, 2015). However, value created by consumers in digital zero-price markets still remains largely unclear, since it is a new phenomenon with different logic of value creation and value capture.…”
Section: Consequently the Purpose Of This Dissertation Ismentioning
confidence: 99%
See 2 more Smart Citations